Comparison of Genomic Characterization in Upper Tract Urothelial Carcinoma and Urothelial Carcinoma of the Bladder. (8th June 2021) - Yang, Kaiwei; Yu, Wei; Liu, Huanhuan; Ding, Feng; Zhang, Yanrui; Zhang, Yun; Wang, Wang; Lou, Feng; Cao, Shanbo; Wang, Huina; He, Zhisong
Abstract : Background: Different genomic characterization in urothelial carcinoma (UC) by site of origin may imply contrasting therapeutic opportunities and pathogenetic mechanisms. The aim of this study was to investigate whether differences between upper tract UC (UTUC) and UC of the bladder (UCB) result from intrinsic biological diversity. Materials and Methods: We prospectively sequenced 118 tumors and matched blood DNA from Chinese patients with UC using next-generation sequencing techniques, including 45 UTUC and 73 UCB. Two hundred twenty-six patients with UTUC and 350 patients with UCB for The Cancer Genome Atlas were acquired from the cbioportal. Results: There were marked disparities in the mutational landscape for UC according to race and site of origin. Signature 22 for exposure to aristolochic acid was only observed in the UTUC cohort. Conversely, signature 6 for defective DNA mismatch repair only existed in the UCB cohort. Compared with UCB, UTUC had higher clonal and subclonal mutation numbers. TP53, PIK3CA, and FGFR3 mutations may be the driver genes for UTUC, whereas for UCB, the driver gene may be BRCA1 . Patients with UTUC had lower PD-L1 than those with UCB. There was no significant difference in the number of DDR mutations, copy number variation counts, and tumor mutational burden between UTUC and UCB. Conclusion: UTUC and UCB exhibit significant differences in the prevalence of genomic landscape and carcinogenesis. Consequently, molecular subtypes differ according to location, and these results may imply the site-specific management of patients with urothelial carcinoma. Mutational signature may be used as a screening tool to assist clinical differential diagnosis between UTUC and UCB. Implications for Practice: This study's findings lay the foundation for a deeper understanding of distinct molecular mechanisms and similar treatment opportunities between upper tract urothelial carcinoma (UTUC) and urothelial carcinoma of the bladder (UCB) and had important implications for the site-specific management of patients with urothelial carcinoma. A comprehensive understanding of the biology of UTUC and UCB is needed to identify new drug targets in order to improve clinical outcomes. Abstract : Because of the relative rarity of upper urinary tract urothelial carcinoma (UTUC), clinical decision-making for patients with this disease is based on treatment data for the more common urothelial carcinoma of the bladder (UCB). This study evaluated molecular differences between the two conditions and explored the potential clinical utility of tumor genomic characterization to guide clinical management through next-generation sequencing.